Chef [videorecording (DVD)] - Favreau, Jon; Favreau, Jon; Favreau, Jon; Vergara, Sofía, 1972-; Leguizamo, John; Johansson, Scarlett, 1984-; Hoffman, Dustin, 1937-; Downey, Robert, Jr., 1965- (Universal Studios, 2014)
A chef who loses his restaurant job starts up a food truck in an effort to reclaim his creative promise, while piecing back together his estranged family.